SATURATION THICKNESSES FOR SCATTERING BREMSSTRAHLUNG OF ELECTRONS WITH Ee = 13 AND 22 MeV FROM FLAT LEAD TARGETS AND THEIR STATISTICAL PROCESSING OF THE DATA DEPENDENCE (Multidisciplinary Journal of Science and Technology, 2026)
In the present work, the dependence of the saturation thickness of the scattered gamma radiation on the detection angles and the orientation of flat targets relative to the direction of the probing beam was observed for the first time.